Geographic Information System Tool for Enhancing Administration of Overweight-Vehicle Permits. Issue 1 (January 2015) - Everett, Stephanie; Athigakunagorn, Nathee; Roshandeh, Arash M.; Labi, Samuel; Sinha, Kumares C.
Highway agencies impose permit fees for overweight vehicles both to recuperate (partially) the consumption cost and to encourage the use of less-damaging loading patterns and vehicle configurations. To provide information for such policies, numerous state and national studies have investigated the impacts of overweight vehicles on the physical and operational condition of highway infrastructure, including the consumption (damage) because of overweight vehicles. These studies, which largely addressed truck size and weight, highway cost allocation, or damage cost estimation, have alluded to the onerous challenge of collating permit data with existing pavement and bridge inventory data. Most previous research has relied on aggregate data to overcome this difficulty. The current study details the use of a geographic information system (GIS) tool developed to determine the infrastructure consumption at a disaggregate level. The tool was used to estimate the infrastructure consumption for individual permit records as part of a larger study that analyzed highway infrastructure consumption and revenue generation associated with overweight-vehicle operations in Indiana. The tool may be used in other contexts to administer overweight-vehicle permits, in addition to its use in impact evaluation. Finally, benefits and implications of using GIS technology in the administration of overweight-vehicle permits are discussed.